2016
DOI: 10.1111/1460-6984.12238
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth delivery of Rapid Syllable Transitions (ReST) treatment for childhood apraxia of speech

Abstract: This phase 1 study provides promising indications of the efficacy of ReST treatment when delivered four times per week via telehealth, and warrants further large-scale investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 30 publications
1
41
0
8
Order By: Relevance
“…In the Australian context, a 2014 Senate inquiry found that not only were there fewer speech-language pathologists (SLPs) working outside urban areas, but also the ratio of therapists per 100 000 people declined as rurality increased (Community Affairs References Committee 2014). Telehealth is one way of addressing some of the barriers associated with staffing and access issues and it has been shown to be an acceptable and viable alternative to face-to-face speech-language services in a range of specialties, including dysphagia assessment and intervention (Collins et al 2017, Sharma et al 2013, stuttering therapy (O'Brian et al 2014, Bridgman et al 2016, and assessment and intervention for speech-sound disorders, including childhood apraxia of speech (Grogan-Johnson et al 2013, Thomas et al 2016, Waite et al 2012. Telehealth has also been used to provide formal assessments of child language with young children with no known language difficulties (Waite et al 2010), as well as children with reading difficulties (Sutherland et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the Australian context, a 2014 Senate inquiry found that not only were there fewer speech-language pathologists (SLPs) working outside urban areas, but also the ratio of therapists per 100 000 people declined as rurality increased (Community Affairs References Committee 2014). Telehealth is one way of addressing some of the barriers associated with staffing and access issues and it has been shown to be an acceptable and viable alternative to face-to-face speech-language services in a range of specialties, including dysphagia assessment and intervention (Collins et al 2017, Sharma et al 2013, stuttering therapy (O'Brian et al 2014, Bridgman et al 2016, and assessment and intervention for speech-sound disorders, including childhood apraxia of speech (Grogan-Johnson et al 2013, Thomas et al 2016, Waite et al 2012. Telehealth has also been used to provide formal assessments of child language with young children with no known language difficulties (Waite et al 2010), as well as children with reading difficulties (Sutherland et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Desses, cinco foram excluídos por não responderem a pergunta norteadora, desta forma um artigo tornou-se elegível segundo os critérios PRISMA utilizados para o desenvolvimento desta pesquisa. Procedeu-se a leitura criteriosa na íntegra do estudo e após a aplicação dos critérios de elegibilidade, o estudo (Thomas et al, 2016) Research, Society and Development, v. 9, n. 11, e1559119685, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9685 A pesquisa (Thomas et al, 2016) -DEAP;Dodd et al 2006 Test of Polysyllables -Gozzard et al 2006 Clinical Evaluation of Language Fundamentals-Preschool Second Edition -(CELF-P2;Wiig et al 2004) ou a versão australiana da 4ª edição (CELF-4;Semel et al 2006) Goldman-Fristoe Test of Articulation 2 -2) (GFTA-2; Goldman e Fristoe 2000)…”
Section: Resultsunclassified
“…Os pais ficaram muito satisfeitos com o tratamento por telessaúde e relataram que seus filhos estavam motivados a participar de sessões de videoconferência. Os clínicos relataram altos níveis de satisfação com o tratamento em telessaúde (Thomas et al, 2016). Os cuidadores e os terapeutasficaram satisfeitos com o tratamento de telessaúde.…”
Section: Resultsunclassified
“…A number of narrative reviews have concluded that therapy for childhood speech and language impairment via telepractice is feasible and valid (149,151,152,(159)(160)(161). However, there are no published systematic reviews describing the use of telepractice for paediatric speech and language screening.…”
Section: Efficacy and Adoption Of Speech Pathology Telepracticementioning
confidence: 99%
“…These studies report that SLPs are often reluctant to provide direct services due to concerns regarding the efficacy of assessment and therapy interventions delivered via telepractice. It is interesting that this perception continues despite a growing evidence base in the area of speech pathology telepractice (32,(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161).…”
Section: Suitability Of Patient Groups and Services For Telepractice mentioning
confidence: 99%